19. CLINICAL CHARACTERISTICS AND SURVIVAL OUTCOMES AFTER CURATIVE SURGERY FOR GASTRIC CANCER AT TRANSPORT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate epidemiological, clinical characteristics, and prognostic factors after curative gastrectomy for gastric cancer at the Transport Hospital.Methods: A retrospective cross-sectional study was conducted on 154 patients diagnosed and surgically treated for gastric cancer between January 2020 and November 2024. Demographic, clinical, laboratory, and pathological data were collected. Survival was analyzed using Kaplan–Meier and multivariate Cox regression to identify prognostic factors.Results: The mean age was 61.7 ± 9.8 years, with 66.2% male patients. Most cases were diagnosed at advanced stages (II–III). Poor general condition (ASA ≥3), low serum albumin, and preoperative anemia were significantly associated with higher postoperative complications and shorter survival (p